(3GdCdaGXs - (3jYbhH Hf ESMGb, CHh jhSa, GHf GdScjJ,J (B224 (3g` s
(3ChdgG (B:s
(3MOKfG CHh Ydi ESeGYjd Hf GdbGSe GdHZOGOi hCfG CfXQ ai fSNJi gPg (B: (3HGH GdZfi hGdNUH s
(3BNQgG (B:s
(3jfJgi HHGH GddHS s
(3GdfSNI HgG MhGTs
(3QhGjI CHh GdYHGS CMeO Hf jMji GdeYQha HKYdH GdeJhai SfI (B291 (3cJHJ Ydi hQb ZRGds
(3bQFJ Ydi GdYGdeI GHf GdSjO GdHWdjhSi ai efRdg HeOjfI HdfSjI YGe (B511s
(3UYH bQGAI fgGjI GdeNWhW ef cKQI GdQWhHI hGdJQbjY s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B195 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B243 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B536s
Keywords: (3GddZIs